(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
This is a historical study on African religious nationalism centered on Simon Toco and Tocoism. The objective is to understand the reasons that led to the marginalization of the study of Angolan Religious Nationalism by the first researchers who devoted themselves to this aspect. Reconstitution made on the basis of colonial documentary funds and through access to the first publications. We identified that the bulwark of the expression of the fight against the Portuguese colonial authorities, was first in Kongo.